Communication in the Real World An Introduction to Communication Studies - Open Textbook Library (Open Textbook Library, 2016)
Communication in the Real World: An Introduction to Communication Studies overviews the time-tested conceptual foundations of the field, while incorporating the latest research and cutting-edge applications of these basics. Each chapter will include timely, concrete, and real-life examples of communication concepts in action. A key feature of this book is the integration of content regarding diversity and organizational communication in each chapter through examples and/or discrete sub-sections. Discussions of diversity are not relegated to feature boxes. Also integrated into the content are examples that are inclusive in terms of race, gender, sexuality, ability, age, marital status, religion, and other diverse identity characteristics.
Chapter 1: Introduction to Communication Studies -- Chapter 2: Communication and Perception -- Chapter 3: Verbal Communication -- Chapter 4: Nonverbal Communication -- Chapter 5: Listening -- Chapter 6: Interpersonal Communication Processes -- Chapter 7: Communication in Relationships -- Chapter 8: Culture and Communication -- Chapter 9: Preparing a Speech -- Chapter 10: Delivering a Speech -- Chapter 11: Informative and Persuasive Speaking -- Chapter 12: Public Speaking in Various Contexts -- Chapter 13: Small Group Communication -- Chapter 14: Leadership, Roles, and Problem Solving in Groups -- Chapter 15: Media, Technology, and Communication -- Chapter 16: New Media and Communication
In English.
Description based on print resource
Keywords: Communication -- Textbooks